Deteritorialisasi Khaos Melalui Permainan Musik Calempong di Nagari Unggan - Fahmi Marh; Selvi Kasman (Institut Seni Indonesia Padangpanjang, 2021)
This article reveals the element of deterritorialization in the sub-culture of the Minangkabau community with the Deleuze concept. The concept of deterritorialization to reveal what the Minangkabau man with the title Datuak Paduko Alam did to the chaos he faced with the loss of a woman is called Mande. The female figure behind the birth of the traditional Minangkabau calempong music game in Nagari Uggan. The musical detritorialization that occurs in Minangkabau society is particularly a part of the life experiences of female calempong players in Nagari Uggan. The purpose of this research using the Deleuze concept is to reveal the past problems of calempong which have deterritorialization elements. However, this is expressed through the experiences of calempong players and stories or stories of life in society. The method used in this research is qualitative data analysis from five players who are really experienced in playing the composition of calempong in Nagari Uggan. The approach used to reveal the experiences and stories of the community is life history ethnography. The results of this study are about how the experiences of female calempong players are able to express their deterritorialization musically, as well as a new form of reading about Minangkabau traditional music problems through women.Keywords: Deterritorialization; calempong; man and woman; Minangkabau.ABSTRAKArtikel ini mengungkapkan unsur deteritorialisasi dalam sub-budaya masyarakat Minangkabau dengan konsep Deleuze. Konsep deteritorialisasi untuk mengungkapkan apa yang dilakukan laki-laki Minangkabau yang bergelar Datuak Paduko Alam terhadap khaos yang dihadapinya terhadap kehilangan perempuan yang disebut Mande. Sosok perempuan yang melatarbelakangi lahirnya permainan musik tradisional Minangkabau calempong di Nagari Unggan. Detritorialisasi yang secara musikal terjadi dalam masyakat Minangkabau secara khusus menjadi bagian dari pengalaman hidup perempuan pemain calempong di Nagari Unggan. Tujuan penelitian dengan menggunakan konsep Deleuze ini adalah untuk mengungkapkan masalah masa lalu calempong yang memiliki unsur deteritorialisasi. Namun hal itu diungkap melalui pengalaman pemain calempong dan cerita atau kisah yang hidup dalam mayarakat. Metode yang digunakan dalam penelitin ini yaitu data analisis kualitatif dari lima orang pemain yang benar-benar berpengalaman dalam memainkan komposisi calempong di Nagari Unggan. Pendekatan yang digunakan untuk mengungkapkan pengalaman dan cerita masyarakat tersebut adalah etnografi life history. Hasil dari penelitian ini adalah tentang bagaimana pengalaman perempuan pemain calempong mampu mengungkapkan deteritorialisai secara musikal, sekaligus sebagai bentuk pembacaan baru masalah musik tradisional sub-budaya Minangkabau melalui perempuan.Kata Kunci: Deteritorialisasi; calempong; laki-laki dan perempuan; Minangkabau.